Review of four major distinct types of human phospholipase A(2) - Vasquez, Alexis M. (Adv Biol Regul, 2017)
The phospholipase A(2) superfamily of enzymes plays a significant role in the development and progression of numerous inflammatory diseases. Through their catalytic action on membrane phospholipids, phospholipases are the upstream regulators of the eicosanoid pathway releasing free fatty acids for cyclooxygenases, lipoxygenases, and cytochrome P450 enzymes which produce various well-known inflammatory mediators including leukotrienes, thromboxanes and prostaglandins. Elucidating the association of phospholipases A(2) with the membrane, the extraction and binding of phospholipid substrates, and their interaction with small-molecule inhibitors is crucial for the development of new anti-inflammatory therapeutics. Studying phospholipases has been challenging because they act on the surface of cellular membranes and micelles. Multidisciplinary approaches including hydrogen/deuterium exchange mass spectrometry, molecular dynamics simulations, and other computer-aided drug design techniques have been successfully employed by our laboratory to study interactions of phospholipases with membranes, phospholipid substrates and inhibitors. This review summarizes the application of these techniques to study four human recombinant phospholipases A(2) in vitro.